Increased circulating fibrocytes are associated with higher reticulocyte percent in children with sickle cell anemia. Issue 3 (30th June 2015) - Karafin, Matthew S.; Dogra, Shibani; Rodeghier, Mark; Burdick, Marie; Mehrad, Borna; Rose, C. Edward; Strieter, Robert M.; DeBaun, Michael R.; Strunk, Robert C.; Field, Joshua J.
Summary: Background: Interstitial lung disease is common in patients with sickle cell anemia (SCA). Fibrocytes are circulating cells implicated in the pathogenesis of pulmonary fibrosis and airway remodeling in asthma. In this study, we tested the hypotheses that fibrocyte levels are: (1) increased in children with SCA compared to healthy controls, and (2) associated with pulmonary disease. Procedure: Cross‐sectional cohort study of children with SCA who participated in the Sleep Asthma Cohort Study. Results: Fibrocyte levels were obtained from 45 children with SCA and 24 controls. Mean age of SCA cases was 14 years and 53% were female. In children with SCA, levels of circulating fibrocytes were greater than controls ( P  < 0.01). The fibrocytes expressed a hierarchy of chemokine receptors, with CXCR4 expressed on the majority of cells and CCR2 and CCR7 expressed on a smaller subset. Almost half of fibrocytes demonstrated α‐smooth muscle actin activation. Increased fibrocyte levels were associated with a higher reticulocyte count ( P  = 0.03) and older age ( P  = 0.048) in children with SCA. However, children with increased levels of fibrocytes were not more likely to have asthma or lower percent predicted forced expiratory volume in 1 sec/forced vital capacity (FEV1 /FVC) or FEV1 than those with lower fibrocyte levels. Conclusions: Higher levels of fibrocytes in children with SCA compared to controls may be due to hemolysis. Longitudinal studies may be able to better assess the relationship between fibrocyte level and pulmonary dysfunction.Pediatr Pulmonol. 2016;51:295–299 . © 2015 Wiley Periodicals, Inc.